2006
DOI: 10.1162/jocn.2006.18.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Brain Activity across the Adult Lifespan

Abstract: A number of theories have emerged to explain the well-studied changes in memory that occur with age. Many of these theories invoke mechanisms that have the potential to affect multiple cognitive domains, in addition to memory. Such mechanisms include alterations in attentional or inhibitory function, or dysfunction of specific brain areas, such as the frontal lobes. To gain insight into these mechanisms, we used functional magnetic resonance imaging to examine brain activity during encoding and recognition tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
240
5
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 445 publications
(297 citation statements)
references
References 86 publications
(96 reference statements)
45
240
5
7
Order By: Relevance
“…There is also evidence that older adults may have difficulty suppressing the default network when on task, suggesting that they may be more prone to interference from mind-wandering, or reflecting on autobiographical memories during an experiment (Grady et al, 2006;Park et al, 2010). The current work suggests that time of testing may impact older adults' ability to effectively modulate these networks.…”
Section: Discussionmentioning
confidence: 71%
“…There is also evidence that older adults may have difficulty suppressing the default network when on task, suggesting that they may be more prone to interference from mind-wandering, or reflecting on autobiographical memories during an experiment (Grady et al, 2006;Park et al, 2010). The current work suggests that time of testing may impact older adults' ability to effectively modulate these networks.…”
Section: Discussionmentioning
confidence: 71%
“…In young adults, DN regions maintain strong functional interconnections during tasks requiring self-reference or theory of mind 101,102 , and also during the resting state 103,104 . Several studies have found that the reduction of DN activity during externally-driven cognitive tasks is less pronounced in old adults, relative to young adults 58,[105][106][107][108][109][110][111][112] . Functional connectivity of the DN also is reduced with age during working memory tasks 113 and during periods of rest 105,[114][115][116] .…”
Section: Box 1 Measuring Activity In Brain Networkmentioning
confidence: 99%
“…Interestingly, intrinsic connectivity during the resting state among nodes of the DN is related to the performance of older individuals on a variety of cognitive tasks 105,106,111,118 . Given that DN modulation is associated with the degree of task difficulty and performance 119,120 , a deficit in the ability to modulate DN activity and functional connectivity with advancing age may be a mechanism for deficient resource allocation to the task at hand, accounting for some age differences in cognitive performance 108 .…”
Section: Box 1 Measuring Activity In Brain Networkmentioning
confidence: 99%
“…Several studies have found that the reduction of DN activity during externally-driven cognitive tasks is less pronounced in older adults, relative to younger adults (Andrews-Hanna et al, 2007;Damoiseaux et al, 2008;Duzel, Schutze, Yonelinas, & Heinze, 2011;Esposito et al, 2008;Grady et al, 2010;Grady, Springer, Hongwanishkul, McIntosh, & Winocur, 2006;Lustig et al, 2003;Miller et al, 2008;Persson, Lustig, Nelson, & Reuter-Lorenz, 2007). Intrinsic functional connectivity within the DN during periods of rest also is reduced in older relative to younger adults (Andrews-Hanna, et al, 2007;Hedden et al, 2009;Park, Polk, Hebrank, & Jenkins, 2010), and age reductions during memory tasks also have been noted (Sambataro et al, 2010;Wang, Li, Metzak, He, & Woodward, 2010).…”
Section: The Default Network (Dn)mentioning
confidence: 99%